Evaluation of Pap smears performed at a basic health unit in the interior of Piauí (Research, Society and Development, 2020)
The present study aims to present data on the performance of the preventive Pap smear, thus contributing to the implementation of targeted campaigns to combat cervical cancer. Retrospective, exploratory, descriptive study, whose methodological procedure was documentary in the evaluation of the database of a Basic Health Unit (BHU). We evaluated data collected on the Pap smear from 2015 to 2018. A reasonable number of women underwent the test in 2015, where many were diagnosed with moderate inflammation and one case with low-grade intraepithelial injury. In 2016, this number decreased and many cases of mild and moderate inflammation were observed. There is an increase in 2017 and 2018. In 2017 there was a considerable increase in moderate inflammation and in 2018 this increase was even more pronounced. The number of preventive exams (Pap smears) performed was discreet. However, it is noteworthy the importance of conducting campaigns to improve the amount of tests in small municipalities, thus fighting cervical cancer. This action should be carried out continuously and involve the various professionals, such as gynecologists, nurses and pharmacists so that they can develop a more effective work, establishing early diagnoses of inflammation and sexually transmitted infections (STIs).